Cruise ship tourism (CABI, 2006)
This book on cruise tourism has been written for a broad audience including students, tourism industry professionals, planners and managers in the cruise industry, and government agency employees. Part I (chapters 1-5) introduces the industry and some of its underpinning aspects, including examination of cruising from geographical, industrial and cultural perspectives. It is completed by an investigation of policy issues, based on the case of Bermuda. Part II (chapters 6-12) focuses on the demand for cruising, including examination of passengers' perceptions of value, trends in the North American market, and passenger expectations and activities. Part III (chapters 13-23) explores the supply side of cruising including cruise destinations and products with examples from around the world. Part IV (chapters 24-32) explores the industry's economic, social and environmental impacts. Part V (chapters 33-38) investigates a selection of industry issues, before the book is brought to a close by a brief discussion of the future of the industry.